DINAMIKA IDENTITAS GAY DI RUANG PUBLIK TOBOALI BANGKA SELATAN - Rahmawan, Alfin Dwi; Sujadmi, Sujadmi (Jurnal Analisa Sosiologi, 2021)
Gay is known as a sexual attraction that is included in the group of Lesbian, Gay, Bisexual, and Transgender (LGBT). It is the practice of same-sex sexual attraction that has been existed for a long time, from various times to this day, whether in big cities or various areas with a rare touch of modernity. This research intends to find out the dynamics of the existence of a gay identity, in which gay identity is usually stigmatized and becomes a marginalized group in society. This research was conducted in Toboali, the Regency of South Bangka. Toboali area is known for many groups of gay that interact and do their activities as the society in general. To analyze this research, it utilizes the theory of Identity by Manuel Castells. The research method used a descriptive qualitative research design. The technique of this research used snowball and also purposive sampling. The snowball technique is utilized to obtain the data from the gay informant, by gaining the data and the informant from the acquired key informant. The technique of purposive sampling is used for the community as a comprehensive data comparison. The result of the finding in the field shows that there are factors forming a gay identity of individual as follow social experience in childhood, lifestyle needs, family disharmony, and also the peers group. The result of the research also points out that the existence of gay identity in Toboali South Bangka in the stage of resistance identity.Keywords: Dynamics, Gay, Identity, Public Area.Â AbstrakGay diketahui sebagai satu ketertarikan seksual yang tergabung ke dalam kelompok Lesbian, Gay, Biseksual, dan Transgender (LGBT). Yaitu praktik ketertarikan seksual sesama jenis yang sudah sejak dulu ada dari berbagai zaman hingga saat ini, baik di kota-kota besar maupun di berbagai daerah yang jarang tersentuh modernitas. Penelitian ini bertujuan untuk mengetahui dinamika eksistensi identitas gay, yang mana identitas gay ini biasanya terstigmatisasi, dan menjadi kelompok termarjinalkan di dalam masyarakat. Penelitian ini dilakukan di Toboali Kabupaten Bangka Selatan. Dimana di daerah Toboali Bangka Selatan diketahui banyak kelompok gay yang berinteraksi dan melakukan aktivitas seperti masyarakat pada umumnya. Untuk menganalisis penelitian ini digunakan teori identitas dari Manuel Castells. Metode penelitian yang digunakan yakni menggunakan desain penelitian kualitatif fenomenologi. Sedangkan teknik yang digunakan dengan teknik snowball dan juga purposive sampling. Teknik snowball digunakan untuk memperoleh data dari informan gay, dengan cara memperoleh data dan informan dari informan kunci yang telah didapatkan. Teknik purposive sampling digunakan untuk kalangan masyarakat sebagai perbandingan data yang komperhensif. Pembahasan dari penelitian ini meliputi, faktor-faktor yang mempengaruhi, pergaulan sosial gay di Toboali Bangka Selatan dan stigma sosial. Hasil dari penelitian ini menunjukkan bahwa eksistensi identitas gay di Toboali Bangka Selatan pada tahap resistance identity.Kata Kunci: Dinamika, Gay, Identitas, Ruang Publik.